Morphometric Character Analysis Kryptopterus bicirrhis, Valenciennes 1840 in Kampar River, Langgam Village, Riau Province - Widya Hidayana; Roza Elvyra; Feby Dwi Restuningsih (Berkala Perikanan Terubuk, 2023)
The study aims to possibility of using morphometric characters to see differences between male and female fish Kryptopterus bicirrhis in Kampar river. This research was conducted in November 2018 – Maret 2019 using the survey method. The number of samples obtained was 60 Kryptopterus bicirrhis 30 male fish had a total length 113-155 mm and 30 female fish had a total length range 130-170 mm. Kryptopterus bicirrhis have most of the growth satus of positive allometric in male and female. Relationship between the total length and morphometric characters shows very weak, weak medium, strong, and very strong.